UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) MATA PELAJARAN MATEMATIKA DI KELAS V SDN 065014 NAMO GAJAH MEDAN TAHUN PEMBELAJARAN 2017/2018 - SEMBIRING, DUWI HARIANI (Jurnal Ilmiah Aquinas, 2018)
Mathematics tends to be difficult to be accepted and understood bystudents, so it is causing the intresting of students about mathematics quite low.The low result of study’s student is to be a base to research, where the purpose ofthis research is to see the improvement of result of study’s students inmathematics. The type of this research is a classroom action research by usingSTAD type cooperative learning model (Student Teams Achievement Division). Itconsists of two cycles which are planning, implementation, observation, andreflection. This research was held at SDN 065014 Namo Gajah Medan. Thesubject of the study was the students of grade V of SDN 065014 Namo GajahMedan, which were 25 students, while the object was using cooperative learningmodel of stad type (student teams achievement division) inMathematics.The datacollection techniques used tests and observations. From the results of dataobtained from the observation of learning implementation , teacher activity incycle I obtained 75 percent and for student activity obtained 71 percent andaverage of the learning outcomes obtained in the first cycle is 69.5. In the secondcycle of teacher activity increased become 78 percent and for student activity alsoincreased become 76 percent whereas for the average student learning outcomesincreased become 78.24.From the results of research can be concluded theimplementation of learning was good and the result of students’ learning increasedafter using the model of cooperative learning type STAD (Student TeamsAchievement Division) on Mathematics subjects especially prime numbers todetermine FPB and KPK in 5th Grade of SDN 065014 Namo Gajah Medan.